Experiments in plant hybridisation - Mendel, Gregor, 1822-1884 (Harvard University Press, 1965)
During the mid-nineteenth century, Johann Gregor Mendel experimented with pea plants to develop a theory of inheritance. In 1843, while a monk in the Augustian St Thomas’s Abbey in Brünn, Austria, now Brno, Czech Repubic, Mendel examined the physical appearance of the abbey’s pea plants ( Pisum sativum) and noted inconsistencies between what he saw and what the blending theory of inheritance, a primary model of inheritance at the time, predicted. With his experiments, which he recored in “Versuche über Pflanzenhybriden” (“Experiments in Plant Hybridization”) in 1865, Mendel discredited the blending theory of inheritance, and from them he proposed laws for inheritance patterns. Despite the fact that Mendel’s work did not define all aspects of inheritance, his ideas and laws contributed to later concepts of traits, specifically that offspring inherit traits from their parents via genes, that an offspring has at least two genetic factors for any given qualitative trait, and that the offspring inherits the genetic factors in equal proportion from both parents.